Internet Protocol Traceback Technique and Signature & Biometric Authentication for Financial Networks - SP, Pawanraj; Kumar, Prasanna M (International Journal of Computer Sciences and Engineering, 2025)
Major bank hacking cases and bank robbery is reported constantly. The digital forensic evidence is the most important thing for incident response. Therefore, this paper proposes IP (Internet Protocol) traceback technique for better digital forensic. The paper considers one of the most important components in the modern banking system, namely the direction related to ensuring the security of customer data. The number of bank cards is rapidly growing, and accordingly the network of automated teller machines (ATMs). There are smart cards, which provide higher reliability than cards with a magnetic line. This system allows the issuance of money to the client only when scanning his face. The explosive usage of mobile devices enables conducting electronic transactions involving direct signature on such devices. Thus, user signature verification becomes critical to ensure the success deployment of online transactions such as approving legal documents and authenticating financial transactions. This paper proposes a critical segment based online signature verification system to secure mobile transactions on multi-touch mobile devices. The system extracts useful features from a user’s signature that describe both the geometric layout of the signature as well as behavioral and physiological characteristics in the user’s signing process. The experimental evaluation provide signature verification and robust to signature forging attacks.